ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERBANKAN INDONESIA (Studi Kasus pada Bank yang Terdaftar di BEI periode 2010-2012) (Students' Journal of Accounting and Banking, 2014)
The purpose of this reseach is to examine influence of Capital Adequacy Ratio, Non Performing Loan, Loan to Deposit Ratio, Net Interest Margin, Operating Expense to Operating Income and Earning Assets Quality through Return On Assets of public banking listed at Indonesian Stock Exchange during 2010-2012. Population of this research are Commercial Bank that resgistered in Indonesian Stock Exchange from 2010 till 2012. Data on this research are coming from Indonesian Stock Exchange (ISX). Sample are choosen by purposive sampling method at least 27 company. Data’s test technique by using multiple linear regression analyze. The results showed that the Net Interest Margin has a positive effect on Return On Assets and Operating Expenses to Operating Income negatively affect the Return On Assets. While the Capital Adequacy Ratio, Non-Performing Loans, Loan to Deposit Ratio and the Earning Assets Quality has no effect on Return On Assets.Keywords: Capital Adequacy Ratio, Non Performing Loan, Loan to Deposit Ratio, Net Interest Margin, Operating Expense to Operating Income, Earning Assets Quality and Return On Asset